National Program for Reducing Air and Environmental Pollution (NPRAEP) Pemerintah Mongolia dalam Menghadapi Polusi Udara di Ulan Bator (2017-2025) - Abdi Surahman; Y. A. Wahyudin; Zulkarnain Zulkarnain (The Department of International Relations Universitas Mataram, 2022)
This research aims to analyze how the implementation of the National Program for Reducing Air and Environmental Pollution (NPRAEP) policy by the Mongolian government in dealing with air pollution in Ulaanbaatar. This study uses Environmentalism Theory and the Green State Concept through the methods of library research in qualitative-descriptive approach. Environmentalism emphasizes the harmony and sustainability of environmental aspects in ensuring human life. In Green State, it refers to the role of the state in ensuring environmental sustainability through greener policies. The results of this study indicate that in green view of NPRAEP policy, it refers to the five main objectives of its implementation including improving air quality in cities and city center, reducing pollution sources through the introduction of environmentally friendly technologies, comprehensive steps to reduce vehicle emissions, management, coordination, and incentives and financing of air pollution activities, and increasing citizen participation and accountability in reducing environmental pollution